Determining the dimensions of essential medical coverage required by military body armour plates utilising Computed Tomography. Issue 9 (September 2016) - Breeze, J.; Lewis, E.A.; Fryer, R.
Abstract: Introduction: Military body armour is designed to prevent the penetration of ballistic projectiles into the most vulnerable structures within the thorax and abdomen. Currently the OSPREY and VIRTUS body armour systems issued to United Kingdom (UK) Armed Forces personnel are provided with a single size front and rear ceramic plate regardless of the individual's body dimensions. Currently limited information exists to determine whether these plates overprotect some members of the military population, and no method exists to accurately size plates to an individual. Method: Computed Tomography (CT) scans of 120 male Caucasian UK Armed Forces personnel were analysed to measure the dimensions of internal thoraco-abdominal anatomical structures that had been defined as requiring essential medical coverage. The boundaries of these structures were related to three potential anthropometric landmarks on the skin surface and statistical analysis was undertaken to validate the results. Results: The range of heights of each individual used in this study was comparable to previous anthropometric surveys, confirming that a representative sample had been used. The vertical dimension of essential medical coverage demonstrated good correlation to torso height (suprasternal notch to iliac crest) but not to stature (r 2 = 0.53 versus 0.04). Horizontal coverage did not correlate to either measure of height. Surface landmarks utilised in this study were proven to be reliable surrogate markers for the boundaries of the underlying anatomical structures potentially requiring essential protection by a plate. Conclusions: Providing a range of plate sizes, particularly multiple heights, should optimise the medical coverage and thus effectiveness of body armour for UK Armed Forces personnel. The results of this work provide evidence that a single width of plate if chosen correctly will provide the essential medical coverage for the entire military population, whilst recognising that it still could overprotect the smallest individuals. With regards to anthropometric measurements; it is recommended, based on this work, that torso height is used instead of stature for sizing body armour. Coverage assessments should now be undertaken for side protection as well as for other non-Caucasian populations and females, with anthropometric surveys utilising the three landmarks recommended in this study.